Hypercalcemia, Anemia, and Acute Kidney Injury: A Rare Presentation of Sarcoidosis - Neeraj Sharma; Hassan Tariq; Kalpana Uday; Yevgeniy Skaradinskiy; Masooma Niazi; Sridhar Chilimuri (Case Reports in Medicine)
We discuss a case of a 61-year-old woman who presented with substernal chest pain. She was found to have elevated calcium levels, anemia, and acute kidney injury. The hypercalcemia persisted despite therapy with fluids and bisphosphonates. She was found to have nonparathyroid hormone (PTH) mediated hypercalcemia. The chest X-ray did not reveal any pathology. Our Initial impression was likely underlying hematologic malignancy such as lymphoma or multiple myeloma. A bone marrow biopsy was performed that revealed nonnecrotizing granulomatous inflammation. Further workup revealed elevated vitamin 1,25 dihydroxy level, beta-two microglobulin level, and ACE levels. Noncontrast computed tomography (CT) scan of chest showed bilateral apical bronchiectasis, but did not show any lymphadenopathy or evidence of malignancy. Subsequently, a fiber optic bronchoscopy with transbronchial biopsy showed nonnecrotizing granulomatous inflammation consistent with sarcoidosis. After initiating glucocorticoid therapy, the patient’s hypercalcemia improved and her kidney function returned to baseline.